Public perceptions towards genetically modified crops and foods in Kenya - Anunda, H.; Njoka, Fredrick M.; Shauri, H. (My University, 2009)
The broad objective of the study was to assess public perception towards Genetically Modified (GM) Crops and Foods in Kenya. The specific objectives were to find out the influence of background factors and Agro-ecological zones on the public perception towards GMCs and Foods in the country. A survey was carried out in Kenya covering all the 8 provinces between November 2007 and June 2008, targeting adult civilian population (aged 18+ years). The researchers set out to attain a sample size of 700 subjects so as to achieve a sampling error rate of +3.7%. Accordingly, four clusters comprising of general consumers, farmers, academicians, and resource persons were selected for the study. Efforts were made to ensure that the sample drawn was representative of the Kenyan population through Simple Random Sampling, Systematic Sampling, Convenient and Snowball Sampling as was appropriate. Data was collected using self administered questionnaires. Specifically, the survey instrument was designed to gather information on the participants’ background, ecological zones and perception towards GMCs and foods. Overall, well over one half (58%) of the respondents had positive perceptions towards GMCs and foods. Further, results of the study indicated that positive perception towards GMCs and foods was significantly related not only to the participant’s demographics but also to their Agroecological zones. Findings of the study suggest the need for a well designed and effective program to create awareness and educate the public about various issues relating to GMCs and foods. Various stakeholder such as the government, scientists, Non Governmental Organizations and the private sector need to communicate proactively with the public, especially women, elderly people etc, with complete and accurate information about GMCs and Foods.
Keywords: Biotechnology; genetic engineering; genetically modified crops; Kenya; perceptions